Efficacy of Applied Relaxation as indicated preventive intervention in individuals at increased risk for mental disorders: A randomized controlled trial. (October 2022) - Beesdo-Baum, Katja; Zenker, Monique; Rückert, Frank; Kische, Hanna; Pieper, Lars; Asselmann, Eva
Abstract: The objective was to examine the efficacy of Applied Relaxation (AR) as indicated preventive intervention to reduce psychopathological symptoms and prevent incident mental disorders. In a parallel-group randomized controlled trial, N = 277 adults with elevated tension/distress, anxiety, or depressive symptomatology (Depression-Anxiety-Stress Scale, DASS-21) but no 12-month DSM-5 diagnosis of any mental disorder assessed via standardized interview (DIA-X-5) were randomized to an intervention group (IG; n = 139) receiving group-based AR training, or an assessment-only control group (CG, n = 138). Self-report questionnaires at baseline, post (immediately after the 10 week intervention or a similar time frame in CG) and 12-month follow-up included the DASS-21 as primary outcome measure of intervention efficacy. Incident subthreshold and threshold mental disorders were assessed via DIA-X-5 at 12-month follow-up as primary outcome of prevention efficacy. Intervention and prevention effects were examined on an intent-to-treat basis with missing data replaced using chained multiple imputation. Mixed-model analyses revealed accelerated symptom improvement in IG versus CG with a medium baseline-to-post between-group effect size (d = 0.59, 95%CI: 0.36–0.82). Logistic regression analysis revealed a significantly lower incidence rate for (sub-)threshold mental disorders until 12-month follow-up in IG (34.7%) versus CG (49.3%; Odds Ratio: 0.54, 95%CI: 0.31–0.92, Risk Ratio: 0.70, 95%CI: 0.51–0.96, Risk Difference = −0.15, 95%CI: −0.28 to −0.02). Group-based AR as a promising indicative preventive intervention should be tested in long-term studies and relative to a credible alternative intervention to assure that the intervention effects are not entirely due to demand characteristics, expectancies, or non-specific effects. Highlights: Applied Relaxation accelerates a decrease of symptoms of stress/tension, anxiety and depression. Applied Relaxation is associated with a decreased 12-month incidence of subthreshold/threshold mental disorders. Age, sex and general symptom severity do not moderate intervention and prevention efficacy except for anxiety symptomatology.